2000
DOI: 10.1016/s0014-5793(00)01302-8
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial cells synthesize and secrete brain‐derived neurotrophic factor

Abstract: Brain-derived neurotrophic factor (BDNF) is an abundant neurotrophin in brain and peripheral nerves, where it affects neural development, survival and repair after injury. BDNF has been detected in rat and human blood, but the source of circulating BDNF is not established. BDNF messenger and peptide were detected in cultured cells and in the culture medium of human umbilical vein endothelial cells. The expression of BDNF was up-regulated by elevation of intracellular cAMP and down-regulated by Ca 2+ ionophore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
254
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(268 citation statements)
references
References 31 publications
(30 reference statements)
5
254
2
1
Order By: Relevance
“…Neurotrophins (BDNF) have been shown to be expressed by some, but not all, endothelial cells in culture (6,8,43). Using brain-derived, immortalized endothelial cells (RBE4 cells) we determined that these cells indeed express BDNF in our threedimensional culture system and that expression is increased following hypoxic treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotrophins (BDNF) have been shown to be expressed by some, but not all, endothelial cells in culture (6,8,43). Using brain-derived, immortalized endothelial cells (RBE4 cells) we determined that these cells indeed express BDNF in our threedimensional culture system and that expression is increased following hypoxic treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies we and others have (3,4) shown that selected angiogenic factors, VEGF 1 in particular, are capable of not only affecting a variety of endothelial behaviors but also are capable of affecting neuronal behavior in a receptor-specific fashion. Interestingly, recent studies have demonstrated that neurotrophins expressed by endothelia and are capable of influencing several endothelial cell functions including endothelial cell survival and vessel stabilization (5)(6)(7) and that endothelial cells may express neurotrophin receptors (8).…”
mentioning
confidence: 99%
“…However, many immune and vascular endothelial cells also produce BNDF (Besser and Wank, 1999;Furuno and Nakanishi, 2006;Kerschensteiner et al, 1999;Kimata, 2005;Nakahashi et al, 2000;Prakash et al, 2009;Rezaee et al, 2010;Ziemssen et al, 2002); serum BDNF also correlates with leukocyte BDNF mRNA (Cattaneo et al, 2009), and systemic levels of BDNF are actually increased during attacks of multiple sclerosis (Liguori et al, 2009). Thus, there may be a complicated relationship between cortical and serum BDNF (Gass and Hellweg, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of foam containing BDNF increased the number of blood vessels at the mid-level of the implant compared to the control foam at 8 weeks after implantation. Blood vessels are formed by endothelial cells, which produce and secrete BDNF [60]. Also, BNDF is a known survival factor for endothelial cells, which express the trkB receptor [61].…”
Section: Discussionmentioning
confidence: 99%